How effective is the invisible hand? Agricultural and food markets in Central and Eastern Europe - Stephan Brosig; Heinrich Hockmann (Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2005)
This volume of proceedings, available both as hard copy and pdf <http://www.iamo.de/dok/sr_vol31.pdf>, is a compilation of selected contributions to the IAMO Forum 2005, which will be held in Halle (Saale), Germany, at the Institute of Agricultural Development in Central and Eastern Europe from June 16-18, 2005. CONTENTS: Agricultural and food markets in Central and Eastern Europe: An introduction; Stephan Brosig, Heinrich Hockmann. Agricultural markets in CEE - An overview; József Popp. Regoverning agrifood markets in CEEC - Poland's pork and apple markets; Jerzy Wilkin, Malgorzta Juchniewicz, Dominika Milczarek. Regoverning markets in the Hungarian dairy sector; Imre Ferto, Csaba Forgács, Anikó Juhász, Gyöngyi Kürthy. Analysis of competitiveness, economic efficiency and distortions in the Estonian milk sector; Piret Hein. Building sustainable supply chains: The role of institutions; Jill E. Hobbs. How effective is the invisible hand on technological and institutional change and the reduction of transaction costs in the food sector? Ernst-August Nuppenau. How effective is the visible hand of the government in stabilising the wheat and flour price relation in Ukraine? Bernhard Brümmer, Sergiy Zorya. Marketing margins and price transmission on the Hungarian pork market; Lajos Zoltán Bakucs, Imre Ferto. Slovenian retailing market structures, retail prices, and size of marketing margins for food staples; Štefan Bojnec. Scarcity and preferences (Data Envelopment Analysis of Moscow region corporate farms); Nikolay Svetlov. Buying or renting in? Selling or renting out? Exploring contract choice on the Polish land market; Annette Hurrelmann. The organisation of buyer - Supplier relations in the food chain: The case of the German fruit processing industry and Polish farmers; Kai Maack. Supply Chain Networks: Analysis based on strategic management theories and institutional economics; Jon H. Hanf. Dynamics of labour market participation: What drives Chinese farmers into and out of off-farm employment? Thomas Glauben, Thomas Herzfeld, Xiaobing Wang. Market channels and commercial orientation in Romania; Borbala Balint. Land reform and the development of agricultural land markets in Russia; Zvi Lerman, Natalya Shagaida. Public quality schemes - Helping ensure well-functioning agri-food markets in Central and East European countries? Eckhard Benner. Competition, market power and antimonopoly policy: A Hayekian perspective; Jürgen Wandel. An ex-ante analysis of a minimum price system for Ukraine; Oleg Nivyevs'ki, Arnim Kuhn
urn:nbn:de:gbv:3:2-4087
Keywords: 330